Prepration and Characterization of Novel Ionoic Polymers to beUsed as Artificial Muscles: Novel ionic polymers for artificial muscles - Mohammad Mahdi Hasani-Sadrabadi,; Seyed Reza Ghaffarian,; Fatemeh S. Majedi,; Homayoun Moaddel, (Iranian Journal of Pharmaceutical Sciences, 2008)
The muscle-like technology would be of enormous advantages for biomedical applications such as medical implants and human assist devices. Ionic polymer metal composites (IPMCs) are one kind of biomimetic actuators. An ionic polymer metal composite composed from an ionomer with high ion exchange capacity that packed between two thin metal layers. In the present study we focused on the preparation of a novel alternative polymeric ionomer to be used as artificial muscles. Sulfonated poly(ether ether ketone) (PEEK) have been synthesized as a new class of ionomeric membrane materials. PEEK was sulfonated at various degrees with sulfuric acid and N,N-Dimethylacetamide as a solvent. Fourier transfer infrared spectroscopy confirmed the quality of substitution reaction. Sulfonated samples showed O-H vibration at 3490 and S=O peaks at 1085 and 1100-1300 cm-1. By increasing degree of sulfonation to 80%, ion exchange capacity, water uptake and the number of water molecules per the fixed sulfone groups (λ) were increased to about 2.4 meq.g-1, 75% and 19, respectively. After calculating the optimum degree of sulfonation, the applications of these ionomers as actuators are studied. Rigid microstructure of PEEK backbone causes to slow displacement. However, this inflexible backbone showed the acceptable tip force during its actuation. These IPMC are easy to prepare and much less expensive than the commercial per-fluorinated membranes such as Nafion®. The results approve the utilization of sulfonated aromatic for artificial muscles applications as novel strong muscles with low flexibility.